2012
DOI: 10.4067/s0717-97072012000100021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protonation Constants of Mercaptosuccinic Acid in Aqueous Solutions of Propylene Glycol and Dioxan

Abstract: The protonation constants values of mercaptosuccinic acid were determined in propylene glycol-and dioxan-water mixtures (0-60% v/v) at 303.0 K at an ionic strength of 0.16 M using pH-metric technique. The protonation constants were calculated with the computer program MINIQUAD75 and selection of the best fit chemical models was based on the statistical parameters. The log K values were found to increase with increase of the organic solvent content. The linear variations of the protonation constants with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The chemisorption of MSA on the Ag + surface is only possible at a slightly acidic pH because then one carboxyl group remains protonated and the other one is deprotonated – carboxylate anion –, leading to hydrogen bonds with surrounding MSA molecules and forming a stable monolayer that coats the Ag 2 Se nanocrystal and reduces surface trap defects. 32,33 This reasoning is only valid for pH 5.0, 33 which led to the highest PL intensities found during the current optimization. Apparently, that mechanism is not limited to this type of semiconductor, as other authors reported the same pH as optimal for other MSA-coated QDs.…”
Section: Resultsmentioning
confidence: 83%
“…The chemisorption of MSA on the Ag + surface is only possible at a slightly acidic pH because then one carboxyl group remains protonated and the other one is deprotonated – carboxylate anion –, leading to hydrogen bonds with surrounding MSA molecules and forming a stable monolayer that coats the Ag 2 Se nanocrystal and reduces surface trap defects. 32,33 This reasoning is only valid for pH 5.0, 33 which led to the highest PL intensities found during the current optimization. Apparently, that mechanism is not limited to this type of semiconductor, as other authors reported the same pH as optimal for other MSA-coated QDs.…”
Section: Resultsmentioning
confidence: 83%
“…However, the PL intensities were drastically reduced at a pH of less than 5.0 and greater than 8.0, as seen from Figure c. It must be mentioned here that the −COOH groups of the MSA ligand remain in the deprotonated form at pH > 4, which enables them to coordinate with the Zn 2+ ions . Additionally, at a higher pH (greater than 8), the Zn 2+ ions form Zn­(OH) 2 , which in turn disentangles the Zn 2+ from the Zn–AgNCs, and consequently, the PL intensity drops sharply .…”
Section: Results and Discussionmentioning
confidence: 99%
“…It must be mentioned here that the −COOH groups of the MSA ligand remain in the deprotonated form at pH > 4, which enables them to coordinate with the Zn 2+ ions. 47 Additionally, at a higher pH (greater than 8), the Zn 2+ ions form Zn(OH) 2 , which in turn disentangles the Zn 2+ from the Zn−AgNCs, and consequently, the PL intensity drops sharply. 45 Furthermore, to investigate the effect of temperature on the PL intensity and thermal stability of aggregated Zn−AgNCs, we carried out the PL measurements as a function of temperature (Figure 5d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%